Perancangan Sistem Terintegrasi pada Aplikasi Siklus Akuntansi dengan Evaluasi Technology Acceptance Model (TAM) - Dwi Ely Kurniawan; Azis Saputra; Purwono Prasetyawan (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2018)
The accounting cycle is used to see the picture of a company's circumstances in decision-making, whether the company gains or loses. The development of information technology at this time developed so rapidly, so the company is required to continue to innovate to improve company performance. Factors that cause information delays, lack of organized information processing and unintegrated data cause the company difficulties in controlling financial flows. This research designs an application of financial accounting cycle using Enterprise Resource Planning (ERP) and Technology Acceptance Model (TAM) approach. ERP is known as an integrated system between business processes with each other while the TAM model to see the factors of user acceptance of business process changes using the application. Based on the results of the design of applications that have been developed with several main criteria obtained the benefit criteria with 75% percentage, convenience criteria with percentage 76.67%, usability criteria with 77.5% percentage, graphic design criteria with percentage 80%, compatibility criterion with percentage 60 % and functionality criteria with a percentage of 72.5%, so it can be concluded that the application is useful, easy to use, but it is easier in controlling and making decisions based on these parameters